In vitro Evaluation of Programmed Cell Death in the Immune System of Pacific Oyster Crassostrea gigas by the Effect of Marine Toxins - Estrada, Norma; Núñez-Vázquez, Erick J.; Palacios, Alejandra; Ascencio, Felipe; Guzmán-Villanueva, Laura; Contreras, Rubén G. (Frontiers in Immunology, 2021)
Programmed cell death (PCD) is an essential process for the immune system's development and homeostasis, enabling the remotion of infected or unnecessary cells. There are several PCD's types, depending on the molecular mechanisms, such as non-inflammatory or pro-inflammatory. Hemocytes are the main component of cellular immunity in bivalve mollusks. Numerous infectious microorganisms produce toxins that impair hemocytes functions, but there is little knowledge on the role of PCD in these cells. This study aims to evaluate in vitro whether marine toxins induce a particular type of PCD in hemocytes of the bivalve mollusk Crassostrea gigas during four h at 25° C. Hemocytes were incubated with two types of marine toxins: non-proteinaceous toxins from microalgae (saxitoxin, STX; gonyautoxins 2 and 3, GTX2/3; okadaic acid/dynophysistoxin-1, OA/DTX-1; brevetoxins 2 and 3, PbTx-2,-3; brevetoxin 2, PbTx-2), and proteinaceous extracts from bacteria (Vibrio parahaemolyticus, Vp; V. campbellii, Vc). Also, we used the apoptosis inducers, staurosporine (STP), and camptothecin (CPT). STP, CPT, STX, and GTX 2/3, provoked high hemocyte mortality characterized by apoptosis hallmarks such as phosphatidylserine translocation into the outer leaflet of the cell membrane, exacerbated chromatin condensation, DNA oligonucleosomal fragments, and variation in gene expression levels of apoptotic caspases 2, 3, 7, and 8. The mixture of PbTx-2,-3 also showed many apoptosis features; however, they did not show apoptotic DNA oligonucleosomal fragments. Likewise, PbTx-2, OA/DTX-1, and proteinaceous extracts from bacteria Vp, and Vc, induced a minor degree of cell death with high gene expression of the pro-inflammatory initiator caspase-1, which could indicate a process of pyroptosis-like PCD. Hemocytes could carry out both PCD types simultaneously. Therefore, marine toxins trigger PCD's signaling pathways in C. gigas hemocytes, depending on the toxin's nature, which appears to be highly conserved both structurally and functionally.